Disparities in HIV Testing, Condom Use, and HIV Education Between Transgender and Not Transgender High School–Aged Youth: Findings From the 2019 Youth Risk Behavior Survey. (February 2023) - Phillips, Gregory; Davoudpour, Shahin; Floresca, Ysabel Beatrice; Felt, Dylan; Curry, Caleb W.; Wang, Xinzi; Choi, Joseph; Kelsey, Scar Winter; Beach, Lauren B.
Transgender individuals are disproportionately affected by HIV in the United States. Given increased risk of HIV among youth, there is a need to understand HIV risk and protective factors among transgender individuals who are 18 years and younger. Patterns of HIV testing, HIV education, and condom use have known associations with HIV outcomes among youth in general, but are understudied among transgender youth. This study assessed these outcomes by developing a series of sex-stratified multivariable logistic regression models using pooled Youth Risk Behavior Survey data. Results indicate female and male transgender youth as well as males who were not sure they were transgender were more likely have tested for HIV compared with their not transgender peers. Male transgender youth were significantly less likely to have received HIV education compared with not transgender males. Females not sure if they were transgender and male transgender youth were significantly less likely to have used condoms compared with, respectively, not transgender female and not transgender male counterparts. In sum, condom use and HIV education both remain lower among transgender individuals relative to their not-transgender peers. This highlights the need for the promotion of culturally appropriate HIV education and HIV prevention supports among transgender youth.